(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
This Randomised controlled clinical trial was undertaken to determine the suitable time of catheter removal after urogenital prolapse surgery in order to reduce the catheter related UTI and its long term sequel. Method: Total 80 patients undergoing vaginal hysterectomy with pelvic floor repair were enrolled and randomised into two equal groups by lottery method. Trans-urethral catheter was removed on 2nd & 5th post operative day in group I (n=40) and in group II (n=40) respectively. Post voidal residual urine volume before operation and after removal of catheter was measured in all patients by ultrasound scanning. Re-catheterisation was done for three more days if residual volume > 200ml after removal of catheter. Urine samples were taken before removal of catheter and send for routine microscopic examination and culture & sensitivity test to detect UTI. Results: Removal of catheter on 2nd post-operative day lead to significant reduction of rate of UTI. The rate of UTI following removal of catheter was 7.5% versus 42.5% in group I and in group II (p<0.001). But need for recatheterisation was significantly higher in group I (15%) than in group II (2.5%). The mean duration of catheterisation was 47.63 (±0.628) and 119.35 (±0.864) hours in group I and group II respectively. Majority of the patients in group I did not require prolongation of catheterisation. Mean duration of hospital stay after operation was 5 days in group I and 7.95 days in group II (p<0.001). Conclusion: Short period catheterisation is associated with lower rate of UTI and shorter hospital stay. Disadvantages of prolonged catheterisation outweigh the advantages. Therefore removal of the catheter on the 2nd post-operative day after genital prolapse surgery is preferable than 5 days catheterization DOI: http://dx.doi.org/10.3329/bjog.v26i2.13782 Bangladesh J Obstet Gynaecol, 2011; Vol. 26(2) : 68-71